'Don't abandon me': Young people's experiences of child and adolescent psychiatric inpatient care supporting recovery described in blogs. (23rd October 2020) - Wallström, Rebecca; Lindgren, Eva; Gabrielsson, Sebastian
Abstract: Child and adolescent psychiatric (CAP) inpatient care has the potential to support or hinder young people's mental‐health recovery. Research describing inpatient care from the perspective of young people is rare. Personal blogs provide an opportunity to further understand how inpatient care relates to young people's recovery processes. This study aimed to explore young people's experiences of CAP inpatient care supporting mental‐health recovery. The study is reported in accordance with the COREQ guidelines. Data were created during 2018 from twenty‐seven personal blogs describing first‐hand experiences of being a patient in a CAP inpatient care facility in Sweden and analysed using a method for interpretive description. Information in blogs suggests they were written by women, a majority of which had experienced eating disorders. Findings describe young people's experiences of CAP inpatient care supporting mental‐health recovery in an interpretive explanation with one theme, 'Don't abandon me', and three sub‐themes: 'Listen to me', 'Believe in me', and 'Allow me to feel safe'. This study adds to the growing body of empirical work suggesting the importance of the concept of recovery in young people's mental health. To support recovery, CAP inpatient care needs to focus on developing the content of care rather than minimizing the length of the stay. User experience should be at the heart of efforts aimed at improving services.